Enhancing hardware and software performance in RFID collisions. Issue 1 (1st January 2020) - Hema, C.; Sankar, Sharmila; Sandhya, M.
Abstract: Radio Frequency Identification (RFID) is a wireless communicable network medium involving the readers and tags. It is now found in supermarkets that store managers use the RFID reader to check the products imported into the store. The reader while scanning the goods retrieves information regarding its quantity, its price and other related information. Here, there are chances for this information to be lost because of the occurrence of RFID reader collisions. This issue might result in financial losses to the markets, which might be left unnoticed unless it is carefully examined. Hence, to overcome the problem of collisions arising in the RFID environment, an algorithm named Dragonfly-based Clustering Protocol (DCP) is proposed. The parameters stated for the selection of a cluster head are namely the reader's throughput, percentage of collision, identification time delay and energy consumption. Thus, a cluster head is chosen from the RFID reader network by DCP followed by Graph coloring algorithm, for scheduling the readers, reading all the tags without missing any values, this helps to produce an effective result with better performance in both software and hardware implementation.